2019
DOI: 10.1080/15384101.2018.1559557
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic slippage: an old tale with a new twist

Abstract: Targeting the mitotic machinery using anti-mitotic drugs for elimination of cancer cells is a century-old concept, which continues to be routinely used as a first line of treatment in the clinic. However, patient response remains unpredictable and drug resistance limits effectiveness of these drugs. Cancer cells exit from drug-induced mitotic arrest (mitotic slippage) to avoid subsequent cell death which is thought to be a major mechanism contributing to this resistance. The tumor cells that acquire resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 76 publications
3
86
0
1
Order By: Relevance
“…The average length a cell spent in mitotic arrest that culminated in death in mitosis was longer than for the cells that underwent slippage, (Fig. 2d), supporting a model of competing pathways between cell death and mitotic exit 22,23 . Additionally, BAD cells showed significantly longer times in mitotic arrest than vector control cells, irrespective of cell fate ( Fig.…”
Section: Resultssupporting
confidence: 55%
“…The average length a cell spent in mitotic arrest that culminated in death in mitosis was longer than for the cells that underwent slippage, (Fig. 2d), supporting a model of competing pathways between cell death and mitotic exit 22,23 . Additionally, BAD cells showed significantly longer times in mitotic arrest than vector control cells, irrespective of cell fate ( Fig.…”
Section: Resultssupporting
confidence: 55%
“…Conversely, we also observed that the overexpression of cyclin E2 increases polyploidy, and this occurs in concert with the downregulation of the preRC protein, Cdt1 ( Figure 7 ). Negative feedback through the proteolysis of Cdt1 is well established as a consequence of increased rereplication [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates the association between CEP55 upregulation and the development and progression of a variety of malignant tumors, including breast tumors, gastric tumors, and lung tumors [13][14][15]. The knockdown of CEP55 can significantly inhibit the viability and proliferation of a tumor cell and even lead to tumor cell death [16,17].…”
Section: Introductionmentioning
confidence: 99%